Peran Komisi Perlindungan Anak Indonesia Untuk Mewujudkan Perlindungan Anak - Arliman S, Laurensius (Faculty of Law Universitas Lancang Kuning, 2018)
KPAI is an independent institution formed based on Presidential Decree Number 77 of 2003 concerning the Indonesian Child Protection Commission. KPAI is the mandate of the Child Protection Law with a view to increasing the effectiveness of child protection. KPAI is a state institution mandated by the Act to oversee and supervise the implementation of child protection. This paper discusses how is the position of the Commission for the Protection of Indonesian Children in the Indonesian constitutional system? What is the function of the Indonesian Child Protection Commission as an independent state commission in carrying out the enforcement of human rights for children according to the mandate of the constitution? This research is a descriptive research. The approach used in this study is a normative juridical approach supported by an empirical juridical approach. The data used in this study are secondary data and primary data. Against all data and materials obtained from the results of the study will be compiled and analyzed qualitatively. The function of KPAI as an independent state commission in carrying out the enforcement of human rights on children according to the mandate of the constitution is reflected in 9 (nine) main fields, namely 1) Social Affairs and Children in Emergency Situations; 2) Family and Care Sector; 3) Civil Rights and Participation Fields; 4) Religion and Culture; 5) Education Sector; 6) Health and Drug Sector; 7) Fields of Pornography and Cybercrime; 8) Field of Children Against the Law (ABH); and 9) Trafficking and Exploitation. Where there are functions that are going well, and some are not good, so KPAI gives a lot of suggestions and criticisms of the 9 (nine) functions it performs.